NEW SOCIAL MOVEMENT AGAINST COVID-19 IN INDONESIA (Socio-Historical Study of Twiterr Social Media During a Pandemic) - Faisol, A Zahid (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Abstract: Social media twitter is seen as a form of transformation of the social movement strategy undertaken by the community to fight and prevent the corona virus that has now entered Indonesian territory. In this case the public through social media twitter spread about health issues and how to prevent the corona virus in Indonesia. Public efforts to carry out social movements are jointly conducting education through the hashtag on Twitter, because as there are many consumptive behaviors in the use of social media, Twitter is one of the ways that is considered fast in conveying a condition or event related to the current corona outbreak has spread to various countries. In this study using descriptive qualitative methods and analyzed using the theory of social movements from Anthony Giddens. It can be concluded that the use of social media Twitter is a form of community efforts to fight against the corona virus through the use of hashtag (#) on Twitter, which has succeeded in moving the community towards efforts to prevent corona virus outbreaks in a short time. Keywords: Social Movement, Twitter Social Media, Corona Virus